2010
DOI: 10.1111/j.1365-2133.2010.09703.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variability associated withWNT10Anonsense mutations

Abstract: IL-17A and IL-17F, which are produced by Th17 cells, were elevated (IL-17A: clopidogrel, 237AE8 pg mL )1 ; control, not detected; and IL-17F: clopidogrel, 187AE3 pg mL )1 ; control, not detected). On the other hand, the serum IL-17A level was below the detection limit (< 60 pg mL )1 ), and the serum IL-17F level was elevated (clopidogrel, 265AE0 pg mL )1 ; control, 120AE2 pg mL )1 ).AGEP is a rare and severe skin eruption, of which 90% of cases are induced by drugs such as antibiotics, calcium channel blockers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 4 publications
(5 reference statements)
1
23
0
3
Order By: Relevance
“…Odonto-onycho-dermal dysplasia (OODD) is an autosomal recessive ectodermal dysplasia which shares with SSPS features like PPK and facial telangiectases, but lacks eyelid cysts. Further reports expanded the mutational and clinical spectrum of WNT10A to include three sporadic patients with features compatible with SSPS (10,(12)(13)(14). Further reports expanded the mutational and clinical spectrum of WNT10A to include three sporadic patients with features compatible with SSPS (10,(12)(13)(14).…”
Section: Letter To the Editormentioning
confidence: 99%
“…Odonto-onycho-dermal dysplasia (OODD) is an autosomal recessive ectodermal dysplasia which shares with SSPS features like PPK and facial telangiectases, but lacks eyelid cysts. Further reports expanded the mutational and clinical spectrum of WNT10A to include three sporadic patients with features compatible with SSPS (10,(12)(13)(14). Further reports expanded the mutational and clinical spectrum of WNT10A to include three sporadic patients with features compatible with SSPS (10,(12)(13)(14).…”
Section: Letter To the Editormentioning
confidence: 99%
“…The proband is a 9-year-old boy of Belgian descent (patient A II-2) with TA of 22 permanent teeth. Only six permanent teeth (16,11,21,26, 36 and 46) developed while his mother reported that her son had a complete deciduous dentition. The upper permanent central incisors are conically shaped and the upper first permanent molars are hypoplastic.…”
Section: Overview Literature Regarding Wnt10a Mutationsmentioning
confidence: 99%
“…Clinical examination proband. In her permanent dentition, she has severe TA of 23 teeth (17, 15, 14 (16,13,23, 33 and 46), two of which have a conical shape and one being hypoplastic. Although her mandible is also retruded, leading to a convex profile, the dished-in appearance is again the most catching feature in her facial profile.…”
Section: Family Cmentioning
confidence: 99%
“…OODD and SSPS share common characteristics, including severe hypodontia, nail dystrophy, palmoplantar keratoderma, smooth tongue, hyperhidrosis, and hypotrichosis. Multiple eyelid apocrine hidrocystomas appear to be pathognomonic for SSPS [Sch€ opf et al, 1971;Fadhil et al, 1983;Megarbane et al, 2004;Castori et al, 2008;Bohring et al, 2009;Nagy et al, 2010;van Geel et al, 2010]. Genotype-phenotype correlations have been demonstrated within WNT10A-associated syndromes by Bohring et al [2009].…”
mentioning
confidence: 97%